Exploring the temporal dynamics of rumen bacterial and fungal communities in yaks (Bos grunniens) from 5 days after birth to adulthood by full-length 16S and 18S rRNA sequencing - Yang, Shuli; Zhang, Guangrong; Yuan, Zaimei; He, Shichun; Wang, Rongjiao; Zheng, Jieyi; Mao, Huaming; Chai, Jianmin; Wu, Dongwang (Frontiers in Veterinary Science, 2023)
Ruminants have a unique compartment in their digestive tract; the rumen, comprising microorganisms that can effectively decompose plant fibers for the host to transform into milk and for growth and development, which is important for their host. The colonization of rumen microorganisms is closely related to the host developmental stage and affects host performance production. In this study, we sequenced the full length of the rumen bacterial and fungal communities in wild grazing yaks at different ages, ranging from 5 days after birth to adulthood using amplicon sequencing. Our results showed that rumen microbial communities of yaks undergo a gradual change from 5 to 180 days after birth, with the bacterial and fungal diversity stabilizing at the age of 2 years. The rumen of adult yaks was the most suitable for the growth and reproduction of most bacteria. Bactria diversity of the yak rumen increased gradually from 5 days after birth to adulthood. With the growth of yaks, different dominated bacteria were enriched in different groups, but Prevotella remained highly abundant in all groups. The yak rumen at 90 days of age was the most suitable for the growth and reproduction of most fungi, and 90 days of age could be a cut-off point for the distribution of fungal communities. Fungal Thelebolus was the firstly reported in yak rumen and was enriched in the yak rumen of 90 days after birth. The most abundant and balanced fungal genera were found in adult yaks, and most of them were only detected in adult yaks. Our study is the first report of both the rumen bacterial and fungi communities in wild grazing yaks at different ages and provides the dynamics of the dominated microbiome with the growth of yaks.